Social mapping of perceived ecosystem services supply – The role of social landscape metrics and social hotspots for integrated ecosystem services assessment, landscape planning and management. (July 2016) - De Vreese, Rik; Leys, M.; Fontaine, C.M.; Dendoncker, N.
Graphical abstract: Highlights: Social landscape metrics describe distribution of perceived ecosystem services (ES). Social landscape metrics point towards social ES hotspots. Social ES hotspots only partially overlap with biophysical and ecological hotspots. Social ES mapping integrates georeferenced stakeholder perceptions in ES assessment. Social mapping brings perceived ES in integrated ES assessment and landscape planning. Abstract: This paper contributes to the discussion on integrating societal considerations, stakeholders' perceptions and laymen knowledge into ecosystem services (ES) assessments. The paper illustrates how social mapping of perceived ES supply (or alternatively demand) can contribute to integrated ES assessment. Based on sketched locations of the, according to 38 respondents, most important ES at the local scale, we describe the perceived ES distribution with social landscape metrics (abundance, diversity, richness, risk, rarity) based on traditional landscape ecology indicators. We illustrate how social landscape metrics can inform ES management and planning and describe how synergies between ES as stated by the respondents differ from calculated synergies (the latter based on correlation coefficients between perceived ES abundance). We present indicators pointing to locations where (multiple) ES synergies are perceived by stakeholders (stated synergy index), and to conflicting ES and ES perceived to be at risk (risk index). Overlapping social ES hotspots based on the social landscape metrics with ES hotspots based on more traditional biophysical modelling (biophysical hotspots) and ecological inventories (ecological hotspots) results in social–ecological or social–biophysical hotspots, coldspots and warmspots relevant for nature and landscape planning, management and governance. Based on an analysis of the overlaps between social, biophysical and ecological hotspots on the one hand, and the contribution of ecological quality, land zoning categories and conservation statuses on the other hand, we discuss the added value of integrating social ES mapping in integrated ES assessment, above ES assessments based on biophysical or ecological attributes. Given the limited overlap between social hotspots and ecological or biophysical hotspots, we conclude that integrating stakeholders' mapping of perceived ES supply (or demand) into ES assessments is necessary to reflect the societal aspects of ES in ES assessments. However, with a limited sample of respondents, there is a risk of collectivisation of respondents' viewpoints as a common, societal stance. Moreover, the social landscape metrics are not suitable for describing the distribution of ES with low perceived abundance. Finally, we explain how social ES assessment can result in mainstreaming ES in planning, policy and practice.